Will narrowing the educational gap between husband and wife alleviate housework inequality: Evidence from China - Peng, Zijian; Wu, Lin (Frontiers in Psychology, 2022)
In the past 20 years, China's educational advantage has undergone a gender reversal. The average educational level of women is higher than that of men. However, the gender difference in housework is gradually expanding, and women are still the main undertakers of housework. Based on the China Family Panel Studies, this study explores the impact of the educational gap between husband and wife on the inequality of housework division and its mechanism. OLS regression model was used to estimate the impact of marital education gap on household inequality. It is concluded that the higher the education level of the husband is than that of the wife, the greater the gender inequality in housework. This conclusion is significant at the level of 0.01. On this basis, the instrumental variable method was used to overcome the endogenous problems and a more accurate conclusion was reached. Every unit of increase in the education gap between husband and wife would increase the degree of household inequality by 0.281 percentage points. Quantile regression provides strong evidence for the results. When the gender time ratio of housework is in the range of 0.8-0.95, the education gap will have an impact on the gender division of housework. After the robustness test and heterogeneity analysis of the model, an intermediary variable was established to discuss the mechanism of the model. The income disparity and the working time gap were proved to be intermediary variables. This study believes that in modern society, the education gap between husband and wife will affect the inequality of housework division by changing the relative income and relative working time of husband and wife. Although the educational advantages of women in the whole society have not changed their role in the division of housework. However, with the narrowing of the educational gap between husband and wife, the degree of inequality in the division of housework has been alleviated, indicating that the improvement of women's education level has alleviated the inequality in the division of housework to a certain extent.